DELAY OF CLEAVAGE OF THE ARBACIA EGG BY ULTRAVIOLET RADIATION - Blum, Harold F. (The Rockefeller University Press, 1950)
While our data do not permit us to state the exact locus or mode of action of ultraviolet radiation in the Arbacia egg, certain general conclusions may be reached. The amount of delay of cleavage of these eggs is determined by two principal factors: (1) The extent of an effect, resulting from photochemical action induced by ultraviolet radiation, which is reversible in a biological sense, the reversibility not being directly dependent upon the process of cell division. (2) The sensitivity of the cell division process to the effects of the ultraviolet-induced photochemical reaction. This factor varies with the stage of cell division, the cell being insensitive during a period corresponding to most of mitosis. It seems likely that these findings may apply to cell division in general, but, since the quantitative relationships observed must, in this case, reflect the integration of two semi-independent factors, the over-all picture may appear quite different for different kinds of cells.